Multispeciality Approach in the Management of Patient with Hereditary Gingival Fibromatosis: 1-Year Followup: A Case Report - T. Ramakrishnan; Manmeet Kaur (International Journal of Dentistry)
Background. Hereditary gingival fibromatosis is a fibrotic enlargement of the gingiva. It may exist as an isolated abnormality or as part of multisystem syndrome. This paper reports a case of 16-year-old male with generalized severe gingival overgrowth, involving the maxillary and mandibular arches and covering almost all teeth. Methods. Periodontal management of gingival enlargement included gingivectomy in both arches except in the lower right molar region where flap surgery was done under general anesthesia. After a 2-month followup period, orthodontic treatment was started with fixed appliances. Monthly periodontal checkups and maintainance (scaling and polishing) were scheduled to control the gingival inflammation. Results. Reevaluation of the patient of surgical treatment after two months did not show any recurrence of condition; however, minimal overgrowth was noted 1 month after the beginning of orthodontic treatment which was treated nonsurgically. Conclusions. Although the risk of recurrence is high with this condition, surgical treatment with correction of malocclusion and regular followup can provide excellent outcome as seen in this case.